EFFECTS OF SWIMMING TRAINING IN OBESITY INSTALLATION IN ADULTS OFFSPRING BORN WITHIN A SMALL LITTER - Bruna Schumaker Siqueira; Stefani Valéria Fischer; Amanda Rocha Fujita; Sabrina Grassiolli (Arquivos do Mudi, 2023)
The excessive supply of energy during pregnancy and breastfeeding period, favors the highaccumulation of white adipose tissue (WAT) throughout life, commonly associated withinsulin resistance (IR), dyslipidemia and cardiovascular disease in adulthood. Chronic aerobicexercises reduce accumulation of WAT, preventing the development of metabolic diseases.On the 2 nd postnatal day, litter size was set to: normal (NL) with 9 pups per mother and small(SL) with 3 pups per mother, was used just male rats. After weaning (21 days), NL and SLrats, were divided into sedentary (Sed) and exercised (Exe), forming 4 experimentalsubgroups; NL Sed , NL Exe , SL Sed and SL Exe . From 22–90 days of life exercised groups performedswimming training 3 times for week during 30 minutes. Litter handling influenced bodyweight, retroperitoneal and mesenteric-WAT (p<0.0001) in adulthood. SL Sed animals showedan increase in these parameters when compared to NL Sed and NL Exe animals (P<0.0001).Swimming training reduced body weight and WAT deposits in NL and SL groups(P<0.0001). SL Sed and SL Exe animals showed elevated glucose values at 2h post-glucose loadwhen compared to NL animals. Kitt was also altered by litter reduction (P<0.0001), with SL Sedanimals had higher Kitt values compared to NL Sed and NL Exe rats. This response wasnormalized in SL Exe group.We conclude that lactational hypernutrition causes obesityassociated with disruption of glucose homeostasis and swimming training normalizes insulinsensitivity but is insufficient to restore glucose homeostasis during glucose tolerance test.